Soberania alimentar: transição da agricultura familiar para a cafeicultura na região do Valle de Tenza, Boyacá, Colômbia - Zambrano, Jennifer Lorena Avendaño (2020)
The region of Valle de Tenza, Colombia, presents a situation of transition from family farming of diverse foods to a coffee farming, with a view to an agribusiness model. To understand the current panorama of food sovereignty in Guateque and Guayatá, cities of Valle de Tenza, socio-economic and cultural aspects were evaluated from questionnaires and semi-structured interviews that were applied to 40 rural families that practice family farming and/or coffee farming. In addition, these same aspects were evaluated in 80 families of urban consumers. In both categories, it was intended to know the perception of the interviewees about the availability of food from agriculture and current food practices in relation to the food practices that existed more than ten years ago, in addition to investigating their knowledge about the traditional culinary of the region. The results of this research show that the peasants have low schooling, little government support, do not have a fixed salary and are poorly organized (few associations participate). There was a decrease in the cultivation of regional foods that are part of the typical dishes of the region and of the local level; the poteco or piquete (adaptation of the cocido boyacense), sancocho, plátanos de fondo, the sagu and corn-based amasijos, among others, were the ones that suffered the greatest reduction. Due to the transformation phenomenon that family farming is going through in the Valle de Tenza region, the most representative regional foods are being replaced by financially more profitable crops, including coffee and some exotic fruits that are having greater acceptance in the local and regional market. It is important to consider that interest in certain crops also declined because the local population does not consume some ancestral foods that were formerly grown. Therefore, as the commercial scenario of these foods is reduced, their cultivation ceases to be financially lucrative, despite having adequate soil for their production. This reduction can generate risks related to the autonomy and guarantee of rights in the production and marketing of food, as well as affecting the availability of food and generating the transformation of the gastronomic identity of Valletenzanos, among other aspects related to food sovereignty.